High-Throughput Field Imaging and Basic Image Analysis in a Wheat Breeding Programme - Walter, James; Edwards, James; Cai, Jinhai; McDonald, Glenn; Miklavcic, Stanley J.; Kuchel, Haydn (Frontiers in Plant Science, 2019)
Visual assessment of colour-based traits plays a key role within field-crop breeding programmes, though the process is subjective and time-consuming. Digital image analysis has previously been investigated as an objective alternative to visual assessment for a limited number of traits, showing suitability and slight improvement to throughput over visual assessment. However, easily adoptable, field-based high-throughput methods are still lacking. The aim of the current study was to produce a high-throughput digital imaging and analysis pipeline for the assessment of colour-based traits within a wheat breeding programme. This was achieved through the steps of i) a proof of concept study demonstrating basic image analysis methods in a greenhouse, ii) application of these methods to field trials using hand-held imaging, and iii) developing a field-based high-throughput imaging infrastructure for data collection. The proof of concept study showed a strong correlation (r = 0.95) between visual and digital assessments of wheat physiological yellowing in a greenhouse environment, with both scores having similar heritability (H2 = 0.85 and 0.76, respectively). Digital assessment of hand-held field images showed strong correlations to visual scores for physiological yellowing (r = 0.61 and 0.78), senescence (r = 0.74 and 0.75) and Septoria tritici blotch (r = 0.76), with greater heritability of digital scores, excluding Septoria tritici blotch. Development of the high-throughput imaging infrastructure allowed for images of field plots to be collected at a rate of 7,400 plots per hour. Images of an advanced breeding trial collected with this system were analysed for canopy cover at two time-points, with digital scores correlating strongly to visual scores (r = 0.88 and 0.86) and having similar or greater heritability. This study details how high-throughput digital phenotyping can be applied to colour-based traits within field trials of a wheat breeding programme. It discusses the logistics of implementing such systems with minimal disruption to the programme, provides a detailed methodology for the basic image analysis methods utilised, and has potential for application to other field-crop breeding or research programmes.